The entring book of Roger Morrice, 1677-1691, Volume II the reign of Charles II, 1677-1685 - Morrice, Roger 1628-1702 (Boydell & Brewer, 2007)
The Entring Book is the longest and richest diary of public life in England during the era of the Glorious Revolution. Spanning the years 1677 to 1691, in nearly a million words, it records the downfall of the House of Stuart. This is a chronicle not only of politics and religion, but also of culture and society, gossip and rumour, manners and mores, in a teeming metropolis risen phoenix-like from the Great Fire. Its author, Roger Morrice, was a Puritan clergyman turned confidential reporter for leading Whig politicians - well-connected, a barometer of public opinion, and supremely well-informed. Written just twenty years after Pepys's Diary, the Entring Book depicts a darker England, thrown into a great crisis of 'popery and arbitrary power'
Title from publisher's bibliographic system (viewed on 29 Sep 2017)
Keywords: Morrice, Roger / 1628-1702 / Diaries; Clergy / England / Diaries; Diarists / Great Britain / Biography; Great Britain / Politics and government / 1660-1714 / Sources; Great Britain / History / 1660-1714 / Sources; Great Britain / Social life and customs / 17th century / Sources